An economically viable ionic liquid for the fractionation of lignocellulosic biomass. Issue 13 (26th May 2017) - Brandt-Talbot, Agnieszka; Gschwend, Florence J. V.; Fennell, Paul S.; Lammens, Tijs M.; Tan, Bennett; Weale, James; Hallett, Jason P.
Abstract : Cost-effective fractionation (pretreatment) of lignocellulosic biomass is necessary to enable its large-scale use as a source of liquid fuels, bio-based materials and bio-derived chemicals. Abstract : Cost-effective fractionation (pretreatment) of lignocellulosic biomass is necessary to enable its large-scale use as a source of liquid fuels, bio-based materials and bio-derived chemicals. While a number of ionic liquids (ILs) have proven capable of highly effective pretreatment, their high cost presents a barrier to commercial viability. In this study, we investigate in detail the application of the low-cost ( ca. $1 kg −1 ) ionic liquid triethylammonium hydrogen sulfate for the fractionation of the grass Miscanthus x giganteus into a cellulose rich pulp, a lignin and a distillate. We found that up to 85% of the lignin and up to 100% of the hemicellulose were solubilized into the IL solution. The hemicellulose dissolved mainly in monomeric form, and pentoses were partially converted into furfural. Up to 77% of the glucose contained in the biomass could be released by enzymatic saccharification of the pulp. The IL was successfully recovered and reused four times. A 99% IL recovery was achieved each time. Effective lignin removal and high saccharification yields were maintained during recycling, representing the first demonstration that repeated IL use is feasible due to the self-cleaning properties of the non-distillable solvent. We further demonstrate that furfural and acetic acid can be separated quantitatively from the non-volatile IL by simple distillation, providing an easily recoverable, valuable co-product stream, while IL degradation products were not detected. We further include detailed mass balances for glucose, hemicellulose and lignin, and a preliminary techno-economic estimate for the fractionation process. This is the first demonstration of an efficient and repeated lignocellulose fractionation with a truly low-cost IL, and opens a path to an economically viable IL-based pretreatment process.